Identification of Brain Areas Associated with Chronic Neuropathic Pain through Hjorth Parameter Analysis of EEG Signals - Asyrafi, Hilman; Handayani, Nita; Ilmawan, Lutfi Budi; Shabir, Fadly; Jamal, Ridwan; Jannah, Miftahul; Arysespajayadi (Jurnal Fisika, 2025)
This study investigates the neurophysiological signatures of chronic neuropathic pain (CNP) through the analysis of EEG signals using Hjorth parameters (Activity, Mobility, and Complexity). We compared EEG recordings from 36 CNP patients with those from 19 healthy controls (HC) under both eyes-open and eyes-closed conditions. Analysis of 19 electrode locations revealed significant differences between the groups across all Hjorth parameters. The Activity parameter showed dramatic elevations in CNP patients across all brain regions, indicating widespread cortical hyperexcitability. Mobility parameters revealed significant alterations particularly in occipital (O2), central midline (Cz), and parietal (Pz) regions, with strong effect sizes (Cliff's delta > 0.7). Complexity parameters demonstrated significant changes in right temporal (T4) and parietal midline (Pz) areas. The combined analysis identified the parietal cortex, temporal regions, occipital cortex, and central midline as key areas associated with CNP, suggesting a distributed network disruption rather than localized dysfunction. These findings contribute to our understanding of the neural mechanisms underlying chronic neuropathic pain and may support the development of objective diagnostic markers and targeted interventions for this debilitating condition.